Weight categories in judo: are the differences only physical? - Stankovic, N.; Miloševic, N.; Stanojevic, B. (Physical Education and Sport, 2024)
This study explores the relationship between weight categories and personality traits among male judokas, focusing on psychological differences alongside well-documented physical and performance-related attributes. The aim was to compare emotional competence, personality traits and perceived self-efficacy across lightweight, middleweight, and heavyweight judo categories. The sample included 28 male judokas with over seven years of training and national competitive success, divided into lighter (n=15; -60kg, -66kg, -73kg and 81kg) and heavier (n=13; -90kg, -100kg and +100kg) categories. Psychological traits were assessed using the Emotional Competence Questionnaire, HEXACO-PI-R, PANAS, and the Perceived Social Self-Efficacy Scale. Statistical analyses included independent samples t-tests, Pearson correlations, and canonical discriminant analysis. The findings revealed significant differences in emotionality, with lightweight and middleweight judokas exhibiting higher levels compared to heavyweights. Heavier judokas displayed lower emotional expressiveness and a lower ability of managing emotions, along with reduced negative affect. In contrast, lighter judokas demonstrated higher openness to experience, conscientiousness, and cooperativeness. Additionally, conscientiousness correlated positively with age. These results highlight the need for tailored coaching approaches to address the distinct psychological profiles of judokas in different weight categories. While heavyweight judokas may require support to identify and manage latent psychological needs, lightweight athletes could benefit from enhanced emotional support.